Pelatihan Analisis Kebijakan Publik bagi Aparatur Desa di Desa Sidomakmur Kabupaten Tulang Bawang Barat - Sulistio, Eko Budi; Fadoli, M. Irsyad; Sumanjoyo, Simon; Apandi, Apandi; Mulyana, Nana (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2023)
One of the important elements that must be possessed so that a village can carry out government functions and maintain the existence of the village is to regulate the lives of village communities through public policy. However, village officials, especially the village head and the Sidomakmur Village Consultative Body, still have low competence in formulating public policies. Therefore, this training seeks to provide knowledge and assistance regarding public policy analysis for Sidomakmur Village officials. This training method is mentoring by providing material and discussions. The results of the training showed that all training participants received significant marks regarding their understanding of public policy. Thus, it can be concluded that the knowledge, understanding and competence of public policy analysis training participants has changed for the better.